Low Back Pain Beliefs and Their Relationships with Low Back Pain-Related Disability in Nurses Working in Mainland China and in Australia - Tan, B.; Smith, Anne; O'Sullivan, Peter; Chen, G.; Burnett, A. (2015)
Beliefs held about low back pain (LBP) can influence treatment outcomes and the development of LBP-related disability. Beliefs are shaped by cultural norms but few cross-cultural studies have been done. This cross-sectional study investigated the back pain beliefs and their associations with disability in 109 Chinese nurses and 165 Australian Caucasian nurses. Chinese nurses held more pessimistic views about the consequences of LBP than the Australian and those with LBP held higher level of fear avoidance beliefs and had higher disability than the Australian nurses with LBP. In both groups, more negativeback pain beliefs were significantly associated with higher disability.